Relationship between principal instructional leadership and teacher readiness for change in implementing school based assessment in Selangor state Malaysia - Abdul Aziz, Nor Azni; Asimiran, Soaib; Foo, Say Fooi; Hassan, Aminuddin (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
The instructional leadership of a principal has a positive effect on teacher readiness for change. As such, the purpose of this study was to examine the relationship between three dimensions of principal instructional leadership and teacher readiness for change in implementing School-Based Assessment (SBA) among secondary school teachers in Selangor. A quantitative correlational design was used to collect the data using an adapted questionnaire to measure principal instructional leadership and teacher readiness for change. Principal instructional leadership was measured using “Principal Instructional Measurement Rating Scale” (PIMRS) by Hallinger, while teacher readiness for change was measured using “Readiness for Organizational Change Scale” by Holt et al. The data for this cross-sectional study was obtained from 402 teachers who were selected through stratified random sampling. Data was analysed using SPSS in the form of mean, standard deviation, and Pearson correlation analysis. The findings show that the level of instructional leadership of the principal as a whole is high with a mean of 3.68 and standard deviation 0.57. The overall level of readiness for change among the teachers is high with a mean of 3.72 and standard deviation of 0.51. Tests to determine the correlation between the dimensions of the mission of school (r = 0.321, p <0.05) and creating school learning climate (r = 0.371, p <0.05) with readiness for change among the teachers show a significant positive but low correlation. Meanwhile, the relationship between managing the teaching program (r = 0.470, p <0.05) with readiness for change among the teachers shows a significant positive but moderate correlation. Overall, this study provides the basis for teacher readiness to face changes and strengthening the educational administration field in enhancing instructional leadership model in schools.